The Future of Library Reference Services: Exploring the Use of AI Voice Assistants by Users in Industry 5.0. - Oladokun, Bolaji David; Peter, Uche Iheanyi; Enakrire, Rexwhite Tega; Ajani, Yusuf Ayodeji (Journal of Library & Information Services in Distance Learning)
This study explores the integration of AI voice assistants in library reference services within the framework of Industry 5.0. A systematic review methodology was employed, guided by the PRISMA framework, to analyze 27 peer-reviewed studies from 2015 to 2025. Findings reveal growing acceptance of AI voice assistants, particularly among digital natives, for routine queries. However, complex, context-dependent questions remain challenging for AI systems. User perceptions are mixed, with appreciation for efficiency tempered by concerns about accuracy, data privacy, and ethical implications. Therefore, libraries must prioritize user education, ethical AI deployment, and collaborative frameworks to align with Industry 5.0 values.